Pengaruh Model Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas 4 di SDN 4 Kuranji - Yulia Hardiyanty; Muhammad Makki; Muhammad Syazali (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low level of mathematical problem-solving ability among elementary school students remains a challenge in improving the quality of mathematics learning. This study aims to determine the effect of the Problem Based Learning (PBL) model on the mathematical problem-solving ability of fourth-grade students at SDN 4 Kuranji. The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population and sample consisted of all 30 fourth-grade students. The instrument used was a mathematical problem-solving test based on four indicators proposed by Polya. Data were collected through pretest and posttest, then analyzed using normality testing, hypothesis testing, and N-Gain score calculation. The results showed that the average pretest score of 28.47 increased to 76.67 in the posttest. The normality test indicated that the data were normally distributed, with significance values of 0.526 for the pretest and 0.365 for the posttest (> 0.05). The hypothesis test yielded a significance value of 0.001 (< 0.05), indicating a significant effect after the implementation of the PBL model. The N-Gain score of 0.677 was categorized as moderate. Therefore, the Problem Based Learning model has a positive and effective impact on improving students’ mathematical problem-solving ability.